Exploring effective negotiations on copyright transfer: a qualitative study of business communication in the creative industries - Mohamad Isa, Siti Fariza; Yasin, Megat Al-Imran (Universiti Pendidikan Sultan Idris, 2023)
Practicing effective negotiation to achieve mutual terms and conditions is among the principles and important elements in business affairs. Therefore, this study explores how effective negotiation can enable any business activity in the creative industry to be executed smoothly while meeting the stakeholders demands. Data were collected through a focus group discussion (FGD) involving four participants related to the creative industry. The interview data were transcribed, and ATLAS.ti was utilized to analyze the data using thematic analysis. The analysis reveals that effective negotiation in conducting business, particularly copyright transfer activities, may increase the commercialization activities in the creative industry. Furthermore, fairness in negotiation creates motivation to resolve a specific problem through negotiation and it is expected to bring impact and expectations onto the parties that are involved in the process. Thus, the study implies that content creators should pay more attention to improving the copyright transfer negotiation to flourish the Malaysian creative industry.